Dichotic listening and manual performance in relation to magnetic resonance imaging after closed head injury. - Levin, H S (1989)
In order to investigate post-traumatic hemispheric disconnection effects, dichotic listening and intermanual tasks were administered to 69 patients who had sustained a closed head injury of varying severity. The manual tasks consisted of naming objects palpated in either hand, transfer of postures from one hand to the other and writing. Consistent with predictions, the degree of ear asymmetry in dichotic listening performance was directly related to the severity of the head injury as reflected by the degree of impaired consciousness. Depth and localisation of parenchymal lesion characterised by magnetic resonance imaging were also related to the degree of ear asymmetry. Parenchymal lesions situated in sites which could potentially interfere with callosal auditory or geniculocortical pathways produced a greater disparity in response to left versus right ear inputs as compared with parenchymal lesions in areas such as the frontal lobes which are purportedly unrelated to asymmetries in dichotic listening performance. The results provide further evidence for the effects of multifocal brain lesions involving the white matter on tasks which require intra and/or interhemispheric integration.